2023
DOI: 10.11113/mjfas.v19n4.2954
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus Contamination in Selected Home-based Food Products Sold Throughout Malaysia

Muhammad Amirun Che Hassan,
Muhammad Nur Shazwan Jamzuri,
Fisal Ahmad
et al.

Abstract: Home-based food was a new trend in food business industry where the sellers’ or the owners’ fully prepared and handled food for sale from their home. This online food business had start blooming since the beginning of the Covid-19 Pandemic due to various factors. Almost every Malaysian can produce and sell foods from their home, even without proper training and knowledge regarding food safety. These products were usually sold on online shopping platform or social media as marketing and ordering tools. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Because of its abundance and the resistance of its spores, B. cereus contaminates nearly all agricultural products and plays a major role in the contamination and spoilage of food products [82,83]. In one of the more recent studies, B. cereus contamination of home products packed in retort pouches and glass jars prepared for sale in Malaysia was assessed [84]. It was found that the B. cereus count of 20% of samples exceeded the acceptable limit (>1 × 10 4 CFU/g).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its abundance and the resistance of its spores, B. cereus contaminates nearly all agricultural products and plays a major role in the contamination and spoilage of food products [82,83]. In one of the more recent studies, B. cereus contamination of home products packed in retort pouches and glass jars prepared for sale in Malaysia was assessed [84]. It was found that the B. cereus count of 20% of samples exceeded the acceptable limit (>1 × 10 4 CFU/g).…”
Section: Discussionmentioning
confidence: 99%